INVENTARISASI BASIDIOMYCOTA DI WANA WISATA UBALAN KEDIRI - Klarisa Dewi Julita; Devi Lestari; Farida Nurlaila Zunaidah (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2016)
Tourist attractions Ubalan source is a favorite tourist spot for kediri’s people besides Simpang Lima Gumul (SLG) and waterfall Dholo. Protected forests in ecotourism Ubalan a habitat for many species of animals, plants and fungi. Different types of fungi can be found in protected forests, and most fungi are found is a group of the phylum Basidiomycota. Various references are made when there are many species of the phylum Basidiomycota which can be exploited but some are classified as dangerous fungi. This study aims to determine the diversity of the phylum Basidiomycota in Ubalan. The research method to determine the location of diversity is observed in the growth of fungi. The study was conducted by dividing into three plots with different temperature and humidity. Of the three most common locations are Clitocybe nebulars with the number 40 which is a species of the phylum Basidiomycota nontoxic. While the least discovered is Lepiota sp with the number one which is a fungus bercaun.